Integrated Scheduling of Vessels, Cranes and Trains to Minimize Delays in a Seaport Container Terminal - Jesús Muñuzuri; Antonio Lorenzo-Espejo; Ana Pegado-Bardayo; Alejandro Escudero-Santana (Journal of Marine Science and Engineering, 2022)
The multiple processes taking place on a daily basis at an intermodal container terminal are often considered individually, given the complexity of their joint consideration. Nevertheless, the integrated planning and scheduling of operations in an intermodal terminal, including the arrivals and departures of trains and vessels, is a very relevant topic for terminal managers, which can benefit from the application of Operations Research (OR) techniques to obtain near-optimal solutions without excessive computational cost. Applying the functional integration technique, we present here a mathematical model for this terminal planning process, and solve it using heuristic procedures, given its complexity and size. Details on the benchmark comparison of a genetic algorithm, a simulated annealing routine and a tabu search are provided for different problem instances.